(untitled) (FORUM: University of Edinburgh Postgraduate Journal of Culture & the Arts, 2018)
This paper explores the gaze as witness in George Shaw’s painting of Tile Hill. Considering Shaw’s process of making in the series ‘Scenes of the Passion’ (1990-2017) the paper addresses the relationship of site, memory and gaze in a negotiation of masculinity and loss in these images.